2022
DOI: 10.1002/admi.202201506
|View full text |Cite
|
Sign up to set email alerts
|

Tannic Acid‐Promoted Deposition of Glucose Oxidase on Titanium Surfaces for Mitigation of Persistent Bacterial Infections

Abstract: Despite significant developments in biomaterials and surgical technologies, healthcare-associated infections (HAIs) caused by bacterial adhesion and growth on the device and implant surfaces still pose a significant risk to patients' well-being. [2] According to statistics, device-related infections account for ≈25% of all HAIs, with substantial consequences on patient mortality and morbidity and the cost of healthcare services. [3] Therefore, it is of growing urgency to find an effective means to combat bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Hydrophilic surfaces have a positive effect on the adhesion of cells, e.g., osteoblasts, which means an increase in the compatibility of the material [23]. It was reported by Cheng et al [24] that tannic acid can be utilized to immobilize glucose oxidase on the surface of biomaterials.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrophilic surfaces have a positive effect on the adhesion of cells, e.g., osteoblasts, which means an increase in the compatibility of the material [23]. It was reported by Cheng et al [24] that tannic acid can be utilized to immobilize glucose oxidase on the surface of biomaterials.…”
Section: Discussionmentioning
confidence: 99%
“…It provides abundant reactive sites and can serve as a versatile platform for material engineering and surface functionalization. Moreover, TA is rich in catechol groups, which exhibit strong affinity for various substrates and can actively inhibit microbial adhesion and colonization [ 26 , 27 ], and play a crucial role in bone tissue engineering. In a previous study on the supramolecular assembly of peptides [ 28 ], we found that polyphenols exhibit multiple synergistic crosslinking interactions with different peptide side groups and that in the interaction ratio between positively charged peptides and polyphenols in the peptide-polyphenol network, other amino acids are stronger.…”
Section: Introductionmentioning
confidence: 99%